2018
DOI: 10.1080/19420862.2018.1504726
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput screening of antibody variants for chemical stability: identification of deamidation-resistant mutants

Abstract: Developability assessment of therapeutic antibody candidates assists drug discovery by enabling early identification of undesirable instabilities. Rapid chemical stability screening of antibody variants can accelerate the identification of potential solutions. We describe here the development of a high-throughput assay to characterize asparagine deamidation. We applied the assay to identify a mutation that unexpectedly stabilizes a critical asparagine. Ninety antibody variants were incubated under thermal stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…58,59 In this work, we have shown that point mutations of select aromatic residues may dramatically reduce viscosity. Advancing these engineered antibodies into clinical development would require assessment and mitigation of immunogenicity risk 60,61 and any manufacturing liabilities, [62][63][64] which are beyond the scope of this study. Indeed, assessment of whether these viscosity-lowering mutants also have improved behavior with respect to other properties affected by protein-protein interactions (e.g., aggregation, opalescence, turbidity) could further streamline the removal of antibody liabilities and provide insight into the interactions involved in these phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…58,59 In this work, we have shown that point mutations of select aromatic residues may dramatically reduce viscosity. Advancing these engineered antibodies into clinical development would require assessment and mitigation of immunogenicity risk 60,61 and any manufacturing liabilities, [62][63][64] which are beyond the scope of this study. Indeed, assessment of whether these viscosity-lowering mutants also have improved behavior with respect to other properties affected by protein-protein interactions (e.g., aggregation, opalescence, turbidity) could further streamline the removal of antibody liabilities and provide insight into the interactions involved in these phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…Our work provides a structural demonstration of how deamidation could affect antibody function. Furthermore, the saturation mutagenesis study results, together with other reports on surprising findings with mutants for deamidation stabilization, 8 indicates that extensive screening of stabilization mutants may be necessary to understand the structure-function relationship of the CDR deamidation sites, and ultimately obtain variants with increased resistance to deamidation for improved developability.…”
Section: Discussionmentioning
confidence: 79%
“…These liabilities include chemical degradations such as oxidation, deamidation, isomerization, and fragmentation. [6][7][8][9][10] Deamidation of asparagine (Asn) residues is a major posttranslational modification that can significantly impact protein structure and function. 11,12 The non-enzymatic modification proceeds via formation of a five-member ring succinimide intermediate, which is subsequently hydrolyzed into a mixture of isoaspartate (isoAsp) and aspartate (Asp).…”
Section: Introductionmentioning
confidence: 99%
“…The development of a protein-based vaccine, therapeutic, or diagnostic reagent for a novel disease requires the screening of numerous expression cassettes, for example, to identify suitable regulatory elements (e.g., promoters) that achieve high levels of product accumulation, a sub-cellular compartment 1 https://coronavirus.jhu.edu/map.html that ensures product integrity, as well as different product candidates to identify the most active and most amenable to manufacturing in plants (Buyel et al, 2013a;Kohli et al, 2015;DiCara et al, 2018;Spiegel et al, 2019;Kerwin et al, 2020).…”
Section: Screening Of Product Candidatesmentioning
confidence: 99%